The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/14473828.2020.1836791
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the role of occupational therapy programmes on the mental health of stakeholders’ transition to e-learning during the COVID-19 pandemic

Abstract: The rise in COVID-19 cases has resulted in the suspension of face-to-face classes in the Philippines. Educational programmes are suddenly expected to shift to e-learning strategies in the delivery of educational instructions. This case report provides a critical reflection on an occupational therapy (OT) programme's e-learning preparedness survey of its stakeholders. Implications on the stakeholders' readiness and confidence in e-learning as it relates to their mental health are discussed. The paper concludes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…There appears to be considerable opportunity yet for programs to leverage on-line and asynchronous learning strategies to supplement or support the lecture and lab components of wheelchair-related content, as has been proposed in several publications [ 20 , 22 ]. It is possible that programs may have begun developing these types of resources during the COVID pandemic [ 50 , 51 ],which occurred subsequent to most of the survey responses.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be considerable opportunity yet for programs to leverage on-line and asynchronous learning strategies to supplement or support the lecture and lab components of wheelchair-related content, as has been proposed in several publications [ 20 , 22 ]. It is possible that programs may have begun developing these types of resources during the COVID pandemic [ 50 , 51 ],which occurred subsequent to most of the survey responses.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has compelled HEIs to switch to the virtual mode of teaching following the lockdown restrictions on physical classes. Such drastic changes in the overall teaching environment may significantly impact the attitude and behaviour of both students and teaching staff (Gomez et al, 2020;Gloria and Uttal, 2020;Murphy et al, 2020). HEIs should design programmes to support their students and staff during this transition to a virtual learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort scores were very comparable in our study aside from cohort 8, which demonstrated atypically low pre-bootcamp scores. We cannot be certain why this particular cohort expressed substantially lower baseline capacity but it is likely that, as the first cohort to experience COVID pandemic-related changes in their professional education program (i.e., largely virtual learning and fieldwork; restrictions during the bootcamp) [ 17 , 18 ], these students had less opportunity to acquire experience or self-efficacy with wheelchair use. Broadly speaking, occupational therapy students have entered the bootcamp with more diverse levels of skill while finishing the bootcamp at relatively similar capacity (typically close to 80%), with larger change scores typically correlating to a lower baseline score.…”
Section: Discussionmentioning
confidence: 99%